Semiotic Analysis: The Interpretation of Visual Sign in Senior High Schools English Textbook Cover - Ni Wayan Swarniti; Ni Made Dwi Utari Pusparini; Komang Satria Wirasa; Paulinus Nanggang; Marselinus Nagot (Humanis, 2025)
This research aims to fill that gap by conducting a comprehensive semiotic analysis of visual signs on the covers of senior high school English textbooks used in Indonesia. This research used qualitative method by using descriptive analysis technique to reveal and describe the meaning on visual signs in the senior high school English textbook cover used through the Pierce’s semiotics theory (1931). The research finds that the pictures and symbols on high school English textbook covers send important messages about culture and learning. They show that English is useful for global communication, understanding other cultures, and personal growth. These images help students see English as important and connected to real life.